Peningkatan Skill Wawancara Narasumber Melalui Pelatihan Jurnalistik Teknik Wawancara Narasumber Pada Siswa SMA 02 Masehi PSAK Semarang - Retno Ayu Wulandari; Nailla Rafa Safitri; Nilot Pramudita Ayu Mahesty; Alif Kurniyanto; Fitrotul Afifah; Abdul Rahman Bin Rahim; Suhariyanto Suhariyanto (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Improving journalistic skills, especially in the context of source interview techniques, is essential in the current digital information era. Journalism training in high school can be an effective means of improving these skills. This research aims to explore the effectiveness of journalistic training in source interview techniques conducted by Communication Science students at Semarang University for students at SMA 02 Masehi PSAK Semarang. The Participatory Action Research (PAR) method was used in this research, which involves observation, planning, action and evaluation. The research results showed a significant increase in students' understanding of various aspects of interview techniques, as well as students' enthusiasm during the training. The evaluation results showed a significant increase in students' understanding of interview techniques. This training makes a significant contribution to improving the quality of journalism education in schools and preparing students to face the demands of the professional world.